Kinetic Effects as the Balancing Factor on α-Cellulose Conversion into D-Glucose in Hydrolysis Process of Pt. Tanjung Enim Lestari Solid Waste Using Oscillated Flow - Haryati, Sri (ASEAN Journal of Chemical Engineering, 2007)
A solution to find the best alternative to minimize industry pollution is very necessary especially in pulp and paper manufacturing. One of the alternatives is using waste as feed that will be converted into chemical compound and fuel. Solid waste from pulp and paper manufacturing that contains lignocellulose which is a biomass has potency to be processed for chemical compounds, such as sugar solution (D-glucose), Furfural, and Acetone-Buthanol-Ethanol (ABE). The solid waste in this research is hydrolyzed generating D-glucose solution. The purpose of this research is to study the variables of α-cellulose conversion kinetics as the balancing factor between α-cellulose conversion and energy and mass consumptions. The value of energy and mass consumptions, along with temperature and acid concentration, can be minimized to get higher conversions. Two processes in this method are the preparation and the hydrolyses of α-cellulose by using delignified feed. The hydrolyses process occurs in the Oscillated Reactor Column. The highest conversion was about 50-55% at 10% of sulfic acid concentration.